Vascular Changes of the Hand of a Collegiate Softball Catcher: A Case Report. Issue 1 (January 2021) - Schippers, Sarah; Simmons, Haley; Lawler, Ericka
Abstract : Case: A Division I collegiate softball catcher presented with discoloration, coolness, and swelling of her left index finger that worsened with sport participation. Upper extremity arteriogram revealed absent flow to the radial aspect of the finger and compromise of the ulnar digital artery distal to the proximal interphalangeal joint. After failing nonoperative management, she underwent periarterial sympathectomy with relief of symptoms. Conclusion: Repetitive trauma to a catcher's hand can result in vascular compromise. When nonoperative measures fail, surgical intervention may be successful. We describe successful treatment using sympathectomy. Surgeons should be able to diagnose this condition and understand treatment options.